2019
DOI: 10.1158/1541-7786.mcr-18-0923
|View full text |Cite
|
Sign up to set email alerts
|

Novel Oral mTORC1/2 Inhibitor TAK-228 Has Synergistic Antitumor Effects When Combined with Paclitaxel or PI3Kα Inhibitor TAK-117 in Preclinical Bladder Cancer Models

Abstract: Advanced bladder cancer is associated with a poor prognosis and limited treatment options. The PI3K/AKT/mTOR pathway is frequently activated in this disease and can be a potential therapeutic target for treatment intervention. We studied the antitumor efficacy of a new targeted therapy, TAK-228 (oral mTORC1/2 inhibitor), in preclinical models of bladder cancer. We evaluated the effects of TAK-228 in combination with a PI3Ka inhibitor (TAK-117) or with chemotherapy (paclitaxel). We used six bladder cancer cell … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 48 publications
(61 reference statements)
0
17
0
Order By: Relevance
“…Resveratrol, curcumin and paclitaxel are bioactive molecules with well documented anti-cancer properties. Their interactions with different genes have established them as a modulator of various cancers [ 27 29 ]. These compounds help in the regulation of the oxidative stress.…”
Section: Introductionmentioning
confidence: 99%
“…Resveratrol, curcumin and paclitaxel are bioactive molecules with well documented anti-cancer properties. Their interactions with different genes have established them as a modulator of various cancers [ 27 29 ]. These compounds help in the regulation of the oxidative stress.…”
Section: Introductionmentioning
confidence: 99%
“…Preclinical models of efficacy, safety and pharmacokinetics (PK) of sapanisertib have largely relied on daily dosing. [19][20][21][22][23] Investigation of different dosing schedules in preclinical efficacy models has demonstrated commensurate tumour growth inhibition with administration of sapanisertib in daily or intermittent dosing schedules. [19][20][21][22][23] These preclinical data generally indicated that efficacy was related to total exposure (i.e.…”
mentioning
confidence: 99%
“…The most important is using only 2D models of uterine sarcomas and carcinosarcoma, such models are easily reproducible and allow to perform isobolographic analysis of relations between tested substances, but on the other hand do not fully reflect behaviour of tumours in vivo . Secondly, the reported project do not include any mechanistic research, partially the activity mechanisms of used compounds were previously described 4 , 5 , 5 , 7 , 26 , 29 , 30 , 33 , 35 but further studies aimed to describe mechanisms of cellular response to combined treatment are strongly indicated.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism of overcoming rapamycin resistance by MLN was revealed by Rodik-Outmezguine et al 4 Further studies confirmedactivity of this substance in i.a. pancreatic and bladder cancer cell lines and xenografts 6 , 7 . At present, MLN undergoes clinical trials in many indications, including solid tumours.…”
Section: Introductionmentioning
confidence: 99%